2018
DOI: 10.1262/jrd.2018-004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pre-maturational culture duration on developmental competence of bovine small-sized oocytes

Abstract: We investigated the effects of pre-maturational (pre-IVM) culture on the developmental competence of small-sized bovine oocytes (110 and < 115 µm). Oocytes were cultured with 3-isobutyl-1-methylxanthine (IBMX) for 0, 5, or 10 h and subjected to in vitro maturation, fertilization, and culture. The cleavage rate (73%) of small-sized oocytes with 5 h pre-IVM was higher than those with 0 and 10 h pre-IVM (61 and 62%, respectively). The blastocyst rate (16%) of embryos derived from small-sized oocytes with 5 h pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
(29 reference statements)
1
4
0
Order By: Relevance
“…Moreover, our previous findings [14] suggested that E 2 production by OCGCs producing matured oocytes after IVM was slightly higher than that of OCGCs producing immature oocytes after IVM. In the present study, the development rate to blastocyst was 9.1% in the high AFC group, and the developmental competence was similar to that of bovine oocytes with < 115 µm in diameter (11.9%) in our previous study [29]. On the other hand, we could not produce blastocysts from the oocytes in the low AFC group, although the cleavage rate after IVF was similar between both groups.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Moreover, our previous findings [14] suggested that E 2 production by OCGCs producing matured oocytes after IVM was slightly higher than that of OCGCs producing immature oocytes after IVM. In the present study, the development rate to blastocyst was 9.1% in the high AFC group, and the developmental competence was similar to that of bovine oocytes with < 115 µm in diameter (11.9%) in our previous study [29]. On the other hand, we could not produce blastocysts from the oocytes in the low AFC group, although the cleavage rate after IVF was similar between both groups.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, we performed 10-h culture of in vivo -grown oocytes with low FSH containing medium before IVM culture (pre-IVM) in the previous study [9]. Also, we reported that pre-IVM improved the developmental competence of bovine oocytes derived from IVG [11] and oocytes with < 115 µm in diameter [29]. In further study, we should examine the effects of E 2 /P 4 ratio during IVG culture and FSH treatment before IVM on the acquisition of developmental competence of in vitro -grown oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…This is not desirable because in MII, the chromatin is poorly acetylated, and needs to be fully closed. Some studies have shown an improvement in the developmental competence of the oocytes from small follicles [5,67,68] when PIVM was used. Then we decided to evaluate the use of scriptaid during PIVM of the oocytes obtained from follicles of 1-3 mm, which is considered less competent than the follicles > 3.0 mm [39,69,70].…”
Section: Plos Onementioning
confidence: 99%
“…When OPU is performed, follicles with more than 2 mm in diameter are generally aspirated, but the number of oocytes harvested is limited [34]. It was also reported that the mean diameter of oocytes collected from follicles with 2–3 mm in diameter was 112.9 µm [33], thus, the improvement of small-sized oocytes (110 to < 115 µm; group VII) should be attempted for the effective IVP [35]. We speculated that oocytes collected by OPU, especially small-sized oocytes, need time for cytoplasmic maturation prior to IVM to acquire developmental competence, and we divided oocytes into small-sized (110 to < 115 µm) and large-sized (≥ 115 µm) oocytes and cultured for 0, 5, or 10 h with 3-isobutyl-1-methylxanthine (IBMX), which prevented the meiotic resumption of bovine oocytes and improved the nuclear maturation and the blastocyst development [36, 37], before IVM culture (pre-IVM).…”
Section: Studies On the Improvement Of Oocyte Developmental Competencementioning
confidence: 99%